2021
DOI: 10.3389/fmars.2021.788307
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Chloroplast Genomes of Thalassiosira Species

Abstract: Thalassiosira is a species-rich genus in Bacillariophyta with important ecological contribution to primary productivity but can also pose negative impact on ecology by developing harmful algal blooms (HABs). However, genomic resources of only a few Thalassiosira species are currently available. Here, we constructed complete chloroplast genomes (cpDNAs) of six Thalassiosira strains (representing six Thalassiosira species T. rotula, T. profunda, T. nordenskioeldii, T. tenera, T. weissflogii, and Thalassiosira sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 86 publications
0
12
1
Order By: Relevance
“…Syntenic analysis of the three Thalassionema species, as well as the pairwise comparison of these three species, all exhibited substantial genome rearrangement events (Fig. 9 ), which was different from previous studies that revealed strong collinearity among the cpDNAs of the same genus [ 47 , 48 ].
Fig.
…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…Syntenic analysis of the three Thalassionema species, as well as the pairwise comparison of these three species, all exhibited substantial genome rearrangement events (Fig. 9 ), which was different from previous studies that revealed strong collinearity among the cpDNAs of the same genus [ 47 , 48 ].
Fig.
…”
Section: Resultscontrasting
confidence: 77%
“…The cpDNAs of different species T. bacillare , T. frauenfeldii and T. nitzschioides varied substantially in the length, ranging from 124,127 bp to 140,121 bp (Fig. 3 , Table 1 ), which is also expected because the lengths of cpDNAs of different species in the same genus can be quite different, such as in genera Thalassiosira and Pseudo-nitzschia [ 48 , 52 ], although cpDNAs of different species within a genus can be remarkably similar such as in genera Skeletonema and Chaetoceros [ 47 , 53 ]. According to previous studies, diatom cpDNAs are particularly labile in size, with the longest cpDNA being 201,816 bp in Plagiogramma staurophorum (MG755792) [ 18 ], and the smallest one being only 111,539 bp in Pseudo-nitzschia multiseries (KR709240) [ 54 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Complete plastome sequences of six coscinodiscophycean diatom species which exhibited rich diversity in cell morphology and cell size ( Figure 1 ) were successfully assembled. These plastomes ranged in size from 120.5 kb in A. curvatulus to 135.8 kb in S. turris , and their G + C content was from 30.37% in S. turris to 32.39% in G. delicatula ( Table 1 ), which were in the range of reported diatom plastomes ( Ruck et al, 2017 ; Liu et al, 2021a , b ; He et al, 2022 ; Wang et al, 2022 ). Similar to the reported diatom plastomes (e.g., Kowallik et al, 1995 ; Oudot-Le Secq et al, 2007 ; Tanaka et al, 2011 ; Hamsher et al, 2019 ), these newly assembled plastomes were mapped as canonical circular quadripartite structures with two IRs separating LSC and SSC.…”
Section: Resultsmentioning
confidence: 95%
“…The genus Nitzschia exhibited highly diverse cpDNA genome arrangements, which was different from many diatom genera including Thalassiosira , Chaetoceros , and Skeletonema , in which the cpDNA genome exhibited high consistency [ 83 , 84 , 85 ]. The genus Cylindrotheca consisted of a small group of marine diatoms, with a few species described, including the existence of cryptic species, such as Cylindrotheca closterium [ 60 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%